THE RELATIONSHIP BETWEEN EMPLOYEE ENGAGEMENT AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR ON EMPLOYEE RETENTION AMONG MILLENNIALS - Emelinda; Budaya, Indra; Ikhsan, Mhd. (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2026)
This study aims to analyze the relationship between employee engagement and organizational citizenship behavior (OCB) and their impact on the retention of millennial employees at PTPN VI Kayu Aro, Kerinci, Jambi. The high turnover rate among millennial employees poses a serious challenge for Indonesia s largest tea plantation company. The study employed a descriptive-associative quantitative approach with 120 millennial employee respondents selected through purposive sampling. The research instruments consisted of a structured questionnaire based on a 1 5 Likert scale adapted from the Utrecht Work Engagement Scale (UWES) for the employee engagement variable, Organ s (1988) scale for OCB, and a retention scale developed from the theory of Mathis and Jackson (2011). Data analysis was performed using multiple linear regression with SPSS version 26. The results of the study indicate that: (1) employee engagement has a positive and significant effect on millennial employee retention (β = 0.412; p < 0.05); (2) OCB has a positive and significant effect on millennial employee retention (β = 0.338; p < 0.05); (3) simultaneously, employee engagement and OCB have a significant effect on millennial employee retention, with an F-value of 47.821 and an R of 0.578. The managerial implications suggest that PTPN VI Kayu Aro needs to strengthen engagement programs based on local wisdom values and foster a culture of OCB as a long-term retention strategy.